Pemikiran Al-Farabi Dalam Pendidikan Islam: Integrasi Ilmu, Akhlak Dan Kesejahteraan Sosial Bagi Gen Z - Lina Nailatun Nadzifah; Nasikhin Nasikhin; Nita Yuli Astuti Nita Yuli Astuti (Publikasi Inspirasi Indonesia, 2025)
Al-Farabi's thoughts on Islamic education provide an important paradigm to face the challenges of the modern era, especially in interacting with Generation Z. As a Muslim philosopher from the Middle Ages, Al-Farabi considered education as a process that forms a complete human being, by integrating intellectual intelligence, moral maturity, and social concern. This study aims to explore Al-Farabi's educational values in the context of integrating science, ethics, and social welfare, and their relevance to the characteristics of Generation Z. Through a descriptive-qualitative approach that focuses on literature studies, it is found that Al-Farabi's educational concept, which emphasizes the synergy between science and morality, is very relevant to forming an adaptive, critical, and ethical generation in this digital era. This article contributes to offering a conceptual framework for the development of a contextual and transformative Islamic education curriculum for Generation Z.